2018
DOI: 10.4049/jimmunol.1700384
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Transcriptomic Response of Primary and Immortalized Macrophages to Murine Norovirus Infection

Abstract: Murine norovirus (NoV) is genetically similar to human NoV and offers both an efficient in vitro cell culture system and an animal model by which to investigate the molecular basis of replication. In this study, we present a detailed global view of host alterations to cellular pathways that occur during the progression of a NoV infection. This was accomplished for both BALB/c-derived RAW264.7 (RAW) cells, an immortalized cell line widely used in in vitro replication studies, and primary bone marrow-derived mac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 79 publications
2
17
2
Order By: Relevance
“…We and others have shown that MNV-infected cells increase the transcription of cytokine (IFN-β, TNF-α, and IL-6) mRNAs (Fig. 4) (56, 57), indicating that pattern recognition receptors (PRRs) such as MDA5 (58) have successfully detected the viral infection and activated an antiviral response against it. Intriguingly, MNV-infected cells do not secrete significant levels of cytokines which would help to overcome and contain the acute infection (Fig.…”
Section: Discussionmentioning
confidence: 93%
“…We and others have shown that MNV-infected cells increase the transcription of cytokine (IFN-β, TNF-α, and IL-6) mRNAs (Fig. 4) (56, 57), indicating that pattern recognition receptors (PRRs) such as MDA5 (58) have successfully detected the viral infection and activated an antiviral response against it. Intriguingly, MNV-infected cells do not secrete significant levels of cytokines which would help to overcome and contain the acute infection (Fig.…”
Section: Discussionmentioning
confidence: 93%
“…We validated DE TE dynamics with the data obtained from four virus strains from two independent studies: a 20-h mouse norovirus (MNV) infection time course in mouse RAW 264.7 cells (GSE96586, Fig S9) (Levenson et al, 2018) and a 24-h IAV time course comparing IAV (H3N2) Brisbane, Udorn, and Perth strains in a human cell line (GSE61517) (Fabozzi et al, 2018) (Fig S10). We witnessed dramatic changes in numbers of TEs changing expression by the first time point across all time courses (Figs S9A-F and S10A-C).…”
Section: Dynamics Of Te Up-regulation During Virus Infectionmentioning
confidence: 99%
“…The 7-d influenza A (GSE49933), 20-h norovirus time course (GSE96586), and three 24-h influenza A (H3N2) strain time courses (Brisbane, Udorn, and Perth; GSE61517) were downloaded from GEO and mapped and quantified identically to other mouse and human virus data sets (Altboum et al, 2014;Levenson et al, 2018). The 7-d IAV time course did not have biological replicates for each time point, so time points that were 1-2 h apart were grouped together as biological replicates for DE analysis using a less stringent significance cutoff (FDR < 0.25) for gene and TE-calling against the uninfected (0 h) time point.…”
Section: -D Influenza 20-h Norovirus and 24-h Iav Strain Infectionmentioning
confidence: 99%
“…We and others have shown that MNV infected cells increase the transcription of cytokine (IFNβ, TNFα and IL-6) mRNAs (Fig. 4) (56, 57) indicating that PRRs like MDA5 (58) have successfully detected the viral infection and activated an antiviral response against it. Intriguingly, MNV infected cells do not secrete significant levels cytokines which would help to overcome and contain the acute infection (Fig.…”
Section: Discussionmentioning
confidence: 86%